P104 Exploring the transcriptomic miRNA signatures of Egyptian Inflammatory Bowel Disease patients. (30th January 2023) - Khaled, M; Hamdy, K; Abou-Aisha, K; Mansour, M
Abstract: Background: Inflammatory Bowel Disease (IBD) is a chronic autoimmune gastrointestinal disease, sub-classified into Crohn's disease (CD) and ulcerative colitis (UC). The two subclasses are characterized by a relapsing-remitting course with an increasingly high incidence and prevalence worldwide. Molecular mechanisms guarding the pathogenesis of these diseases remain, to the present day, ambiguous to researchers. MicroRNAs are 22 nucleotides long small noncoding RNAs that have been recently described as essential participants in immune cell development and the immune response to pathogens. During the past decade, genetic and epigenetic studies in IBD have been labeled as essential; since endoscopic assessment and biopsies provide limited data concerning early disease activity, factors for relapse, and response to treatment. To the best of our knowledge, IBD research has never addressed miRNA profiles in Egyptian CD and UC patients as compared to unaffected controls. Methods: Therefore, this study aims to profile miRNAs in Egyptian patients suffering from UC and CD, using RNA-seq of total RNA extracted from colonoscopically obtained tissue pinch biopsies. Results: The sequencing results showed that 30 miRNAs were uniquely expressed in tissue biopsies obtained from the CD patients, as compared to only 14 uniquely expressed in UC patients. Further web-based functional enrichment analysis showed that the miRNAs- in both disease groups- are mainly involved in six interlinked molecular pathways; including the JAK/STAT, WNT, PI3K/AKT, FOXO, MAPK, and NF-κB signaling pathways. One of the most interesting findings of the current study is the fact that the downregulation of the miR-204-5p in UC patients (log2 FC= 5.05)-as compared to CD patients- may be caused by the sponging effect of the MALAT1 long non-coding RNA (lncRNA); affecting related signaling pathways such as the Wnt/β-catenin signaling. This suggests an essential interplay between miRNAs and lncRNAs in shaping the molecular pathogenesis of UC vs. CD. Conclusion: The results of the current study revealed explicit-previously undetermined- differences in the miRNA profiles of patients suffering from UC and CD. Such results are expected to impact the understanding of the difference in the molecular pathogenesis of IBD subtypes affecting patients' response to treatment.